Wisma amfirst, Petaling Jaya - Roslan, Liyana Emyra; Mohamad Zaili, Izzati Zahidah; Mohd Kamaruzaman, Mohamad Hakimi; Wan Khairul Faizi, Wan Muhammad Harith Haiqal (2024)
Wisma Am FIRST is located within SS7, Kelana Jaya and it is easily accessible from Kuala Lumpur City Centre through the North Klang Valley Expressway (NKVE), Lebuhraya Damansara-Puchong (LDP), and Federal Highway. The office building comprises two tower which is Tower 1 and Tower 2 which have 16-storey purpose-built office towers sitting a top 5-storey podium block and one level of basement parking.